2009
DOI: 10.1007/s11739-009-0245-4
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of procalcitonin for diagnosis of infective endocarditis

Abstract: The aim of this study was to evaluate the accuracy of procalcitonin (PCT) in predicting infective endocarditis (IE). 23 adult patients with IE, 30 patients with sepsis and 30 with tick-borne encephalitis were included in this prospective study. The PCT serum level, C-reactive protein (CRP), total leukocyte, and immature polymorphonuclear (PMN) cell counts were determined on admission, prior to the institution of antibiotic therapy, and compared according to the diagnosis. The median PCT level in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
2
17
1
1
Order By: Relevance
“…In total, six original studies and a meta-analysis evaluating PCT, were included here [5,6,[8][9][10][11][12]. Some studies argue for [5,11], and some against [6,[8][9][10], PCT routine testing of IE suspected patients to diagnose or exclude the condition. Two studies found the IE-group to have significantly increased PCT values compared to controls, such as 6.56 ng/mL vs. 0.44 ng/mL [11] and 0.21 ng/mL vs. 0.14 ng/mL [10].…”
Section: Procalcitonin (Pct)mentioning
confidence: 99%
“…In total, six original studies and a meta-analysis evaluating PCT, were included here [5,6,[8][9][10][11][12]. Some studies argue for [5,11], and some against [6,[8][9][10], PCT routine testing of IE suspected patients to diagnose or exclude the condition. Two studies found the IE-group to have significantly increased PCT values compared to controls, such as 6.56 ng/mL vs. 0.44 ng/mL [11] and 0.21 ng/mL vs. 0.14 ng/mL [10].…”
Section: Procalcitonin (Pct)mentioning
confidence: 99%
“…Lastly, Jereb et al [49] evaluated the accuracy of procalcitonin (PCT) in predicting infective endocarditis (IE) in 23 adult patients with IE, 30 patients with sepsis and 30 with tick-borne encephalitis. sPCT level, C-reactive protein (CRP), total leukocytes, and immature polymorphonuclear (PMN) cell counts were determined on admission, prior to the institution of antibiotic therapy, and compared according to the diagnosis: the study fails to demonstrate the superiority of PCT as a diagnostic laboratory parameter in predicting IE compared to CRP.…”
Section: Procalcitonin After Cardiac Surgerymentioning
confidence: 99%
“…13) However, CRP is easier to measure in a blood sample than interleukin-6 in a general hospital. Jereb, et al 15) compared the accuracy of procalcitonin and CRP in diagnosing IE, but they failed to demonstrate superiority of procalcitonin as a diagnostic laboratorial parameter in predicting IE. 12,15) Based on these facts, we believe that a change in the time course of serum CRP levels is more suitable to guide therapeutic decisions in active IE than other indices.…”
Section: Discussionmentioning
confidence: 99%